Modeling soil erosion susceptibility and LULC dynamics for land degradation management using geoinformation technology in Debre Tabor district, Northwestern highlands of Ethiopia - Mulualem Asfaw Ejegu; Endalkachew Sisay Yegizaw (Journal of Degraded and Mining Lands Management, 2021)
Land degradation manifested in landscape change is triggered by soil erosion and it is a thoughtful environmental threat. Nationally, soil loss costs 23% of the national annual GDP. Thus, identifying and prioritizing land degraded areas for conservation in regional planning and resource conservation is the priority of land degradation management. Therefore, identification of erosion hazard area and land use and/or land cover (LULC) dynamics are the overall objectives of the study. GIS and Remote Sensing technology was used to identify erosion hazard areas. K-factor, R-factor, LS factor, P-factor, and C-factor, parameters were derived from mean rainfall, Digital Elevation Model, soil map, LULC map, and ground truth points of all the parameters used to identify erosion hazard areas. At the last, the aggregate effect of those parameters had been analyzed and erosion hazard areas were identified. The Revised Universal Soil Loss Equation (RUSEL) was employed to estimate the annual soil loss of the area. The analysis result unveils that within 20 years interval cultivated land, urban land, and bare land show that a dramatically increasing and forest land shows that decreasing rate. The district has undergone significant changes. Portions of the study area that has the highest slope gradient, the highest amount of rainfall, and consist of Nitosols on agricultural land are the most erosion hazard areas. Statistically, nearly 49%, 19.78%, 9.58%, and 5.45% of the study area coverage lower than moderate, high, very high, and severe soil erosion class correspondingly. Annually losses on average of 41.07 t ha-1yr-1 soil loss because the area is intensively cultivated and experiences relatively high rainfall, and steep slope. The share of the study area, southern part, and northeastern portion of Debre Tabor district are exposed to high erosion hazard class compared to other parts.